Uni-directional ATES in high groundwater flow aquifers - Silvestri, Valerio; Crosta, Giovanni; Previati, Alberto; Frattini, Paolo; Bloemendal, Martin (Geothermics, 2025)
•Numerical study on ATES feasibility in high groundwater flow regimes.•Evaluation of the efficiency related to hydrogeological and operative parameters.•Comparison of ATES well configuration for variable groundwater regime.•Reduced thermal perturbation downstream compared to other geothermal systems. Aquifer thermal energy storage (ATES) is attained by storing thermal energy in aquifers, using the groundwater as a carrier for the heat. Hence, in ATES systems, the background groundwater flow velocity may affect the efficiency if a significant amount of stored heat is moved away from the storage well by advection. This paper presents an alternative solution to the typical “pump and dump” open-loop shallow geothermal system configuration using the ATES concept with a reversed extraction-injection well scheme. This particular placement is able to increase the energy efficiency of a conventional open-loop system while reducing the thermal impact downstream the system. The uni-directional ATES pumping scheme compensates the heat transport by groundwater flow extracting the groundwater from the downstream well and re-injecting back in the upstream well. This research presents a numerical feasibility study and sensitivity analysis of the effects of the well spacing, pumping scheme and groundwater flow velocity on the efficiency of a uni-directional ATES. Optimal combinations are suggested to ensure the maximum re-capture by the downstream well of the heat injected in the upstream well in the previous season and subject to thermal transport by advection, with a maximum heat recovery between 55 and 75 % depending on the conditions. The results of the modelling analysis showed that the optimal inter-well distance depends on the groundwater flow velocity and the total annual storage volume. This paper also demonstrates the mitigation effect of the thermal perturbation downstream of a uni-directional ATES compared to a conventional open-loop scheme.